Spaces of Privacy in Early Modern Dutch Egodocuments - Green, Michaël (TSEG - The Low Countries Journal of Social and Economic History, 2021)
While the word 'privacy' itself only started to appear in the Dutch language in the newspapers of the nineteenth-century, Michaël Green  argues that the idea underlying it was already developing in the early seventeenth century in Dutch contexts. In his article, Green examines, first, transformations that occurred in the seventeenth century in architectural idealizations of the family house, where plans for corridors started to appear alongside locks and separate rooms. Then, based on several examples of egodocuments - among them the diaries of the schoolmaster David Beck and an autobiographical piece by Maria de Neufville - he focuses on how members of the middling and elite classes wrote about their own practical experiences of spatial and emotional privacy.